2016
DOI: 10.1038/nmeth.4101
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of spatially varying mechanical properties in developing tissues

Abstract: It is generally believed that the mechanical properties of the cellular microenvironment and their spatiotemporal variations play a central role in sculpting embryonic tissues, maintaining organ architecture and controlling cell behavior, including cell differentiation. However, no direct in vivo and in situ measurement of mechanical properties within developing 3D tissues and organs has been performed yet. Here we introduce a technique that employs biocompatible ferrofluid microdroplets as local mechanical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
305
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(321 citation statements)
references
References 55 publications
12
305
4
Order By: Relevance
“…This hypothesis is supported by recent in vivo measurements in zebrafish using oil microdroplets. This study found the PSM is more viscous and has a higher elastic modulus than the PZ (Serwane et al, 2017). Importantly, the solidifying columns of paraxial mesoderm are responsible for advancing the posterior growth of the embryo (Dray et al, 2013; Zhou et al, 2009; Zhou et al, 2010; Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This hypothesis is supported by recent in vivo measurements in zebrafish using oil microdroplets. This study found the PSM is more viscous and has a higher elastic modulus than the PZ (Serwane et al, 2017). Importantly, the solidifying columns of paraxial mesoderm are responsible for advancing the posterior growth of the embryo (Dray et al, 2013; Zhou et al, 2009; Zhou et al, 2010; Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…Future experiments examining other cell adhesion molecules, cell polarity and cytoskeletal tension will determine whether these cell biological properties are regulated at this transition and how these local cell biological processes give rise to tissue biomechanics. For example, quantification of in vivo tissue viscosity found that PZ domain is more fluid in cadherin 2 mutants (Serwane et al, 2017). More broadly, symmetry maintenance entails the cross-scale emergence of organism-level order from regulated disorder at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of this method is that it is difficult to decouple surface from deep cell/tissue properties. Ferrofluid oil Droplets (FDs): FDs are inserted between the cells of a tissue, and their initial spherical shape is deformed generating a local force dipole upon the application of an external uniform directional magnetic field (Serwane et al, 2017). A visible or monochromatic laser light is scattered upon interaction with acoustic waves that are spontaneously induced by density fluctuations within a sample (phonons, microscopic sounds waves).…”
Section: Rheologymentioning
confidence: 99%
“…Another study employed magnetically responsive ferroluid microdroplets to measure local mechanical properties in developing embryos. Their results suggested that tissue mechanics might play a critical role in morphogenesis [39].…”
Section: Tissue Engineering and Scafold Mechanical Propertiesmentioning
confidence: 99%